2013
DOI: 10.1111/fwb.12125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retention site on breakdown of organic matter in a mountain stream

Abstract: Summary Organic matter inputs to streams can be retained in contrasting sites, from small leaf packs on top of cobbles to thick organic deposits trapped by wood jams. Differences in environmental conditions and in stability among sites can affect the biological communities, the quality of organic matter and its use by consumers. We measured the accumulation and composition of coarse organic matter and the breakdown of alder leaves on the surface of the streambed, inside gravel bars and in thick litter deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 60 publications
3
25
0
3
Order By: Relevance
“…In general, reference sites exhibit features that match with shredders demands, like litter accumulation and lower temperatures due riparian vegetation presence. Accumulated allochthonous organic matter can provide food for shredders and the positive correlation between these elements is well-established in temperate ecosystems (Richardson, 1992;Wallace et al, 1999;Rowe and Richardson, 2001;González and Graça, 2005;Flores et al, 2013). In this manner, as our studied sites are in the same well-preserved rainforest and accumulated leaves were not restricted to dense riparian covered sites, shredder biomass and abundance seem not restricted as well.…”
Section: Longitudinal Patterns In Shredders and Leavessupporting
confidence: 53%
See 1 more Smart Citation
“…In general, reference sites exhibit features that match with shredders demands, like litter accumulation and lower temperatures due riparian vegetation presence. Accumulated allochthonous organic matter can provide food for shredders and the positive correlation between these elements is well-established in temperate ecosystems (Richardson, 1992;Wallace et al, 1999;Rowe and Richardson, 2001;González and Graça, 2005;Flores et al, 2013). In this manner, as our studied sites are in the same well-preserved rainforest and accumulated leaves were not restricted to dense riparian covered sites, shredder biomass and abundance seem not restricted as well.…”
Section: Longitudinal Patterns In Shredders and Leavessupporting
confidence: 53%
“…The stock of litter in streams can often reflect the organic matter input from adjacent vegetation (Bilby and Likens, 1980;Swanson et al, 1982), and exhibit similar patterns (Bambi et al, 2017). However, the presence and persistence of terrestrial material in the streambed is also related to several factors including composition, organization and densities of trees, seasonality and channel morphology (Fleituch, 2001;Gonçalves et al, 2006a;França et al, 2009;Tank et al, 2010;Flores et al, 2013;Lisboa et al, 2015;Bambi et al, 2017). Therefore, even with variation among sites in the degree of canopy cover and leaf input (Tab.…”
Section: Longitudinal Patterns In Shredders and Leavesmentioning
confidence: 99%
“…Additionally, several studies that have used a larger mesh size for the fine‐mesh treatment have reported a potential confounding factor, as these bags are often entered by small‐sized shredders (McKie, Petrin & Malmqvist ; Flores et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The use of coarse and fine bags is recommended by Gessner & Chauvet (2002) and 5 mm and 0.5 mm mesh size bags have been broadly used in decomposition experiments and allows for distinguishing the relative importance and contribution of microbial decomposers from overall decomposition keeping the same environmental conditions (e.g. Flores et al, 2013;Ferreira & Canhoto, 2014;Mariluan et al, 2015). The bags were placed in the streams on November 21, 2011.…”
Section: Decomposition Experimentsmentioning
confidence: 99%